FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PENGGUNAAN APD PADA PETUGAS LABORATORIUM RUMAH SAKIT PHC SURABAYA - Arta Novita Harlan (Universitas Airlangga, 2017)
Laboratory workers had high risk of being exposed to biological factors such as HIV/AIDS, HBV, HCV viruses and mycobacterium tuberculosis germ. It was obligatory to protect laboratory workers from all contagious diseases by using Personal Protection Equipment (PPE).This researchhad done to learnfactors related to laboratory workers behavior of PPE usage at PHC Surabaya Hospital. This was a descriptive observational research with cross-sectional design. Sample of this research was total population of all PHC Surabaya Hospital laboratory workers (medical analyst/health analyst) in June 2014. Data were taken by questionnaires, observation and interview. The independent variables were predisposing factors (age, sex, time worked, education level, knowledge and attitude), enabling factor (the availability of PPE), reinforcing factors (regulation/policy, socialization, monitoring and reward and punishment). The dependent variable was behavior of PPE usage. The result of this research was acquiredthat 53,3% respondents were < 31 years, 73,3% respondents was woman, had time worked about 5 – 10 years,80% respondents had education level diploma, 86,7% respondent had good knowledge and 53,3% respondents had good attitude, 60% respondents stated that the availability of PPE were laboratory coats, gloves, and masks, 86,7% respondents stated that there was socialization, 73,3% respondents stated that there was monitoring and 80% respondents stated that there wasn’t punishment. The younger age, the lower time worked, and more complete the availability of PPE, the better the behavior of PPE usage.Keywords: PPE usage, laboratory worker, hospital